1995
DOI: 10.1103/physrevlett.74.3491
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis, Discrete Memory, and Nonlinear Wave Propagation in Rock: A New Paradigm

Abstract: The structural elements in a rock are characterized by their density in Preisach-Mayergoyz space (PM space). This density is found for a Berea sandstone from stress-strain data and used to study the response of the sandstone to elaborate pressure protocols. Hysteresis with discrete memory, in agreement with experiment, is found. The relationship between strain, quasistatic modulus, and dynamic modulus is established. Nonlinear wave propagation, the production of copious harmonics, and nonlinear attenuation are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
150
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(161 citation statements)
references
References 12 publications
4
150
1
6
Order By: Relevance
“…The consequence is the impossibility to perform quantitative reproducible and precise experiments if ones modify the applied static stress on the sample, even if it is measured to be equal after a back and forth modification. Moreover, if one would be able to apply exactly the same stress, the memory effects due for instance to the hysteresis in the quasistatic stress-strain relationship, take place [25,26,27]. In an attempt to control carefully the granular preparation, the acoustics of compaction has been recently studied [28].…”
Section: Methodsmentioning
confidence: 99%
“…The consequence is the impossibility to perform quantitative reproducible and precise experiments if ones modify the applied static stress on the sample, even if it is measured to be equal after a back and forth modification. Moreover, if one would be able to apply exactly the same stress, the memory effects due for instance to the hysteresis in the quasistatic stress-strain relationship, take place [25,26,27]. In an attempt to control carefully the granular preparation, the acoustics of compaction has been recently studied [28].…”
Section: Methodsmentioning
confidence: 99%
“…Experimental findings have demonstrated that fast dynamic effect is related to hysteresis in the strain-stress relationship [16]. After Guyer et al [17] a phenomenological model to describe the hysteresis in the Preisach-Mayergoyz space [18] can be written as:…”
Section: Nonlinear Impact Resonant Acoustic Spectroscopymentioning
confidence: 99%
“…45,46 The physical origins of these phenomena, which are still not completely understood, comes from a rearrangement of grains ͑dislocations, rupture, recovery bonds͒ which can be modeled as friction and/or clapping, together with a thermoelastic effect. 47 The "hysteretic" regime ͑except slow dynamics effect͒ of these materials has been modeled phenomenologically by Guyer and McCall,48,49 using the Preisach-Mayergoyz space ͑PM space͒. We choose the description of this model, as it is one of the most simple and universal to introduce nonlinear elasticity in diverse materials/systems.…”
Section: Theorymentioning
confidence: 99%